Design, simulation, and experiment for the end effector of a spherical fruit picking robot - Ziyue Li; Xianju Yuan; Zhanpeng Yang (International Journal of Advanced Robotic Systems, 2023)
The end effector characterizing a flipping–cutting way is designed firstly for picking spherical fruits with a good universality, which is mainly composed of three parts such as a clamping mechanism, a flipping mechanism, and a cutting mechanism. Subsequently, the kinematics simulation for the clamping mechanism, flipping mechanism, and cutting mechanism will be implemented by mathematical models and the ADAMS software, and results reflected through them are consistent with each other, thus presenting the feasibility of the structural scheme and two models. On the basis of scheme and results of models, the sample of the end effector is manufactured. Finally, picking experiments in a lab will be also conducted in view of diverse indexes, such as the successful grabbing action, flipping–cutting action, flipping–breaking action, average fruit picking time, success rate, and damage rate. It is drawn from experimental results that the success rate of grabbing is 100%, and a success rate for picking is over 80%. An average picking time is about 9.6s, and very few fruits are damaged. Therefore, such a scheme is feasible, further presenting a good reference for designing the entire robot in a field of picking diverse spherical fruits.